2021
DOI: 10.1016/j.enbuild.2020.110616
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and optimization of the performance of the heating system in a nZEB educational building by monitoring and simulation

Abstract: The optimal control of the HVAC system in the nearly zero energy buildings (nZEBs) can be considered as a challenge.Indeed, the lack of data given by monitored data does not allow understanding what are the implications of different strategies on thermal comfort and energy consumptions. This paper determines an approach for the evaluation of the management of the heating system in an existing educational nZEB. The aim is to understand how the energy efficiency of the heating system is sensitive to controls str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Temperatures were monitored at the room exhaust diffuser at 1-minute intervals using VAISALA GMW90 sensors [69] that measure temperatures between -5°C and 55°C with an accuracy of ±0.5°C. Apart from these measurements, continuous logging of the parameters like supply and return air temperatures, operation signal of the AHU, IEC, NNV, VAVs etc., was done using the BMS [70]. The Modelica model was validated under normal operating conditions without shocks (NS=base case) and a shock case (30-minute power outage) [68].…”
Section: Experimental Model Validationmentioning
confidence: 99%
“…Temperatures were monitored at the room exhaust diffuser at 1-minute intervals using VAISALA GMW90 sensors [69] that measure temperatures between -5°C and 55°C with an accuracy of ±0.5°C. Apart from these measurements, continuous logging of the parameters like supply and return air temperatures, operation signal of the AHU, IEC, NNV, VAVs etc., was done using the BMS [70]. The Modelica model was validated under normal operating conditions without shocks (NS=base case) and a shock case (30-minute power outage) [68].…”
Section: Experimental Model Validationmentioning
confidence: 99%
“…Ferrara et al [10] proposed a method based on deep residual learning, aimed at simplifying the nZEB optimization design, and the results showed that the use of this simulation method can effectively improve energy efficiency with low accuracy error. Borrelli et al [11] developed a building energy model for optimal control of Heating, Ventilation, and Air Conditioning (HVAC) systems in nZEB using a classroom located in Belgium as a case study. Experimental results showed that based on a combined outdoor time-by-time and thermal storage tank temperature control scheme, energy consumption can be significantly reduced (32-64%), and thermal comfort time was increased (0.6-3.4%).…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies report that the results of simulation models in the design phase rarely match the measured performance, calling this deviation, the "energy performance gap" [20]. The possible causes are manifold, ranging from deviations between actual user loads and their predictions, different characteristics of HVAC systems, startups and shutdowns of HVAC systems [21], etc. Regardless of the error of the simulation software itself, the general solution proposed by the researchers to reduce this gap is to use as much real data as possible, from the building characteristics of its envelopes, accuracy when modeling spaces and the environment, and from outside conditions of the building, e.g., the climate [22,23].…”
Section: Introductionmentioning
confidence: 99%